Building maintenance problems in industrialised building system and conventional constructed building in student accomodation in a Malaysian Public University - Hitam, Ahmad Hafizd (2015)
Building maintenance is now associated with investment return and value of the building itself. The larger the capital needed to construct a building, the greater return is expected. Maintenance costs of a building over its lifespan can cope with the cost of construction for a new bUilding. Therefore, the maintenance is a very important aspect that needs attention and focus as early as its planning stage. Decision making at the level of planning, design and construction methods will have effect on the costs and maintenance works for the building lifespan. The main goal of maintenance is to reduce and minimize the failures and defects of the elements and building equipment effectively and systematically. Indirectly, all aspects of safety and comfort will be guaranteed not only to consumers but also to the owners and organizations. The method of construction and materials used are able to avoid the cost of periodic maintenance especially in a long term period. One of the contemporary debated methods is an integrated construction,known as the Industrialized Building System (IBS). This study is carried out to identify the maintenance activities that occurred to buildings constructed with different methods, which is IBS and conventional delivery. Therefore two buildings were selected as the case studies for this research, namely Thirteenth College representing IBS construction, while Kolej Pendeta Za'ba as a conventional method of construction. The scope maintenance activities investigated includes structural defects,design defects, construction defects, internal fixtures, electrical installation,plumbing and drainage system. This study used survey and interview methods for data collection. A total of 150 questionnaires were distributed to the residents of each college. The questionnaires were distributed to the students of each building in order to get the overall perception regarding the maintenance activities, whereas the interviews were conducted among the industry practitioner in order to get the professional point of view regarding the SUbject matter. For data analysis, this research used descriptive analysis and Independent Samples T-Test to evaluate which bUilding system is more efficient in tackling the maintenance problems. the results showed that defects in the building do occur at each building and there are no significance differences between the two. In conclusion, the selection method of construction of a building either ISS or even conventional does not affect the defects of the building. The findings from this research may benefit to government agencies,constructions player and future researchers on development of the residentsbu ilding in order to minimize the maintenance activities.